2001
DOI: 10.1093/ajcn/74.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anemia with microencapsulated ferrous fumarate plus ascorbic acid supplied as sprinkles to complementary (weaning) foods

Abstract: Use of ferrous sulfate drops or a single daily dose of microencapsulated ferrous fumarate sprinkles plus ascorbic acid resulted in a similar rate of successful treatment of anemia without side effects. To our knowledge, this is the first demonstration of the use of microencapsulated iron sprinkles to treat anemia. Improved ease of use may favor the use of sprinkles to deliver iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
135
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 19 publications
5
135
0
11
Order By: Relevance
“…However, all mothers were instructed not to give more than one sachet a day. The content of Sprinkles sachets was identical for all groups and included 12.5 mg elemental iron as microencapsulated ferrous fumarate, 5 mg zinc as zinc gluconate, 300 mg retinol equivalents as retinol acetate, 160 mg folic acid and 50 mg vitamin C. The rationale for delivering 60 sachets to all children was based on the demonstrated efficacy of a twomonth daily supply of Sprinkles (Zlotkin et al, 2001(Zlotkin et al, , 2003Hirve et al, 2007;Hyder et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all mothers were instructed not to give more than one sachet a day. The content of Sprinkles sachets was identical for all groups and included 12.5 mg elemental iron as microencapsulated ferrous fumarate, 5 mg zinc as zinc gluconate, 300 mg retinol equivalents as retinol acetate, 160 mg folic acid and 50 mg vitamin C. The rationale for delivering 60 sachets to all children was based on the demonstrated efficacy of a twomonth daily supply of Sprinkles (Zlotkin et al, 2001(Zlotkin et al, , 2003Hirve et al, 2007;Hyder et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy, bioavailability and safety of Sprinkles have been demonstrated in many diverse settings (Zlotkin et al, 2001(Zlotkin et al, , 2003Tondeur et al, 2004;Giovannini et al, 2006;Sharieff et al, 2006). For example, a recent field trial in India showed that a daily iron dose of 12.5 mg given as Sprinkles over a two-month period significantly increased haemoglobin concentrations and successfully treated anaemia (Hirve et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Sprinkles berupa zat besi yang dienkapsulasi yaitu zat besi dalam bentuk ferrous fumarate dilapisi dengan lipid untuk mencegah zat besi berinteraksi dengan makanan sehingga tidak terjadi perubahan warna, rasa, dan tekstur makanan. Sprinkles berbentuk serbuk yang ditabur dan dicampurkan langsung ke dalam makanan yang telah disiapkan oleh ibu atau pengasuh anak.…”
unclassified
“…Micronutrien sprinkles merupakan terobosan dalam memenuhi tantangan global untuk mengurangi anemia masa kanak-kanak akibat defisiensi besi dan mikronutrien lainnya. 7 Studi efikasi di Ghana, Afrika Barat tahun 1998-2001 pada anak anemia umur 6-18 bulan selama 2 bulan pengobatan membuktikan bahwa sprinkles (80 mg elemental Fe dalam bentuk ferrous fumarate) sama efektifnya dengan sirup besi (40 mg elemental Fe dalam bentuk Fe sulfat) untuk mengatasi anemia pada 60% sampai 75% bayi anemia di daerah endemik malaria. Persentase kesembuhan dari iron ferrous fumarate sprinkles pada anemia (58%) tidak berbeda dengan sirup iron sulphate drops (56%) (p = 0,51).…”
unclassified
See 1 more Smart Citation